Return to play after hamstring injuries in football (soccer): a worldwide Delphi procedure regarding definition, medical criteria and decision-making - van der Horst, N.; Backx, F. J. G.; Goedhart, E. A.; Huisstede, B. M. A. (British Journal of Sports Medicine, 2017)
There are three major questions about return to play (RTP) after hamstring injuries: How should RTP be defined? Which medical criteria should support the RTP decision? And who should make the RTP decision? The study aimed to provide a clear RTP definition and medical criteria for RTP and to clarify RTP consultation and responsibilities after hamstring injury. The study used the Delphi procedure. The results of a systematic review were used as a starting point for the Delphi procedure. Fifty-eight experts in the field of hamstring injury management selected by 28 FIFA Medical Centres of Excellence worldwide participated. Each Delphi round consisted of a questionnaire, an analysis and an anonymised feedback report. After four Delphi rounds, with more than 83% response for each round, consensus was achieved that RTP should be defined as `the moment a player has received criteria-based medical clearance and is mentally ready for full availability for match selection and/or full training`. The experts reached consensus on the following criteria to support the RTP decision: medical staff clearance, absence of pain on palpation, absence of pain during strength and flexibility testing, absence of pain during/after functional testing, similar hamstring flexibility, performance on field testing, and psychological readiness. It was also agreed that RTP decisions should be based on shared decision-making, primarily via consultation with the athlete, sports physician, physiotherapist, fitness trainer and team coach. The consensus regarding aspects of RTP should provide clarity and facilitate the assessment of when RTP is appropriate after hamstring injury, so as to avoid or reduce the risk of injury recurrence because of a premature RTP.